Considering the Organizational Effectiveness of Maritime Sector SMEs in Indonesia from the Perspective of Knowledge Management, Entrepreneurship Orientation, and Organizational Learning - Rini Safitri; Bayu Ilham Pradana (AIBPM Publisher, 2022)
This research is motivated by the fierce business competition in the maritime sector in Indonesia. In order to compete and grow, SMEs in the maritime sector need to manage knowledge management from the very beginning to learn their environment. Supported by an entrepreneurial orientation and organizational learning, SMEs that have good knowledge management are expected to become effective organizations in achieving their goals. This research belongs to the type of explanatory research using saturated samples in maritime business SMEs. The population comes from four different SMEs in Jakarta and Bandung from 4 SMEs engaged in the maritime sector. The data was processed using the Partial Least Square method due to the limited sample using STATCAL software. The results of this study are: There is a direct influence of Knowledge Management on Entrepreneurial Orientation. Knowledge Management effect on Organizational Learning. However, Knowledge Management does not have impact to the Organizational Effectiveness. And the last, Knowledge Management has an effect on Organizational Effectiveness through Entrepreneurial Orientation and Organizational.Â Keywords: Maritime Sector SMEs, Organizational Effectiveness, Knowledge Management, Entrepreneurship Orientation, Organizational Learning.